Differences between tactical/technical models of coaching and experience on the instructions given by youth soccer coaches during competition - Viciana, J.; Mayorga-Vega, D. (Journal of Physical Education and Sport, 2014)
The aim of this study was to compare the instructions that coaches deliver to their youth soccer players in competition, depending on their experience and model of coaching. The non-probabilistic sample was made up by 10 volunteer youth soccer male coaches (from 25 to 44 years old, and from four to 15 years of experience in soccer). Eighteen coaches of several Andalusian soccer clubs were interviewed, and finally 10 of them were willing to participate in the study. One regional competition match for each coach was recorded, which was a total of 10 matches and 932 minutes analyzed. The young players who participate in this study were between 14 to 18 years old, and they were a total of 125. Qualitative (inducing thematic categories from the transcribed instructions) and quantitative (comparing the independent variables) methodologies were used. Twenty-three categories grouped in seven dimensions were identified. The results showed that the experience and the model of coaching (tactical approach or technical approach) have an influence on coaches` instructions to their players in competition, mainly in emotional and tactical dimensions. The appearance of non-desirable instructions in the youth soccer setting was discovered, with higher frequency in less experienced and technical coaches. Some recommendations to change these results are suggested.